WirelessHART process control with smith predictor compensator - Miya, H.S. (American Scientific Publishers, 2016)
Control over WirelessHART in the recent years has become interestingly attractive to researchers both in the academia and the industry. This is because it offers a more reduced cost and less complexity. However, this is at the cost of increased delays and uncertainties in the system caused by WirelessHART transmitters. The use of conventional PID controllers in a delayed network also leads to instability. In this paper, the Smith predictor technique which can adequately handle dead time by predicting a delay free model of the process is employed. The comparison of the simulation results for both plants considered showed that performance of the Smith predictor is better than that of the optimized PI and PID controllers in terms of percentage of overshoot, settling time and error. Â© 2016 American Scientific Publishers. All rights reserved.